(untitled) (Research, Society and Development, 2022)
Introduction: The orbit is the bony structure around the eyes. When one or more bones around the eyes are broken, it is called an orbital fracture. This results from more violent traumas such as headbutts, falls or car accidents. Treatment is specific to each case. In more serious situations, surgeries are performed. Objective: To analyze the number and variables of hospitalization rates for trauma to the eye and orbit. Methodology: This is a quantitative and retrospective study with data collection from the Department of Informatics of the Unified Health System - DATASUS. The research was carried out using information from vital statistics in the Hospital Morbidity Group of the SUS (SIH/SUS). Data available from the CID 10 for both sexes, age groups and region with the highest incidence were analyzed. Results: During the study period, 129,962 cases of hospitalization due to trauma to the eye socket were found. Regarding gender, 72.97% of the cases are male and 27.03% are female. Of the age groups, deaths are more prevalent among those aged 50 years and over in the age group with 56.06% of total cases of death, with 48.29% in the Southeast region with the highest cases of notifications. Conclusions: It appears, therefore, that the number of deaths from trauma to the eye and orbit are more prevalent in males, especially in the age group from 20 to 29 years of age, with a marked emphasis on the southeastern region of the country.